Challenges Faced by Dairy Producers for Pursuing Sustainable Livelihood in Mullaithivu District - Shivany, S.; Sathana, V.; Piriya, M. (International Conference on Dry Zone Agriculture, The Faculty of Agriculture, University of Jaffna Sri Lanka, 2016)
Dairy farming contributes to the rural economy by the way of production of organic fresh milk, milk based products, and the addition to the supply of draught power (bio-gas). It also ensures the supply of valuable nutrients and provides self-employment opportunities to the people. The fresh milk productions are identified in Mullaitivu as a livelihood source and uplift the living standards of resettled families through government and non-government projects. This district was badly affected by the thirty-year conflict, which ended in May 2009. People were subjected to multiple displacements and numerous lost their livelihoods. Several people in Mullaithivu district have transformed their livelihoods, for their subsistence. Many rumors stated that the dairy farmers in this district have bearable livelihood, but in real it has not been accomplished, even though they are experienced in dairying and crop agriculture, and many assistances were offered. Many initiations both from the government and private sector considers this district as an important area should be developed. Even though there are many initiations in this district, peoples are not satisfied and have not recovered from the recession. Many academician considered many reasons as challenges for this underdevelopment of economics. This study focuses to identify the challenges faced by diary producers for pursing sustainable livelihood for development through their livelihood as dairy production. Data were collected from 35 dairy farmers through Participatory Rural Appraisal Method (PRA) via qualitative methodology. This applied marketing researched categorized the challenges as marketing problems, investment problems, problems for managing cattle, lack of research in dairy production, social and cultural barriers, and the lack of networking system. There are many weaknesses identified at the farmers’ level for achieving their target. Lack of integrated system in diary sector management in post conflict areas should be linked in into a social network system for managing livelihood at sustainable level.
Keywords: Dairy producers; investment; Participatory Rural Appraisal (PRA), sustainable livelihood, social network system, self-employment